Penyuluhan Pencegahan Penyakit Rabies Pada Sekaa Teruna Teruni Kecamatan Selemadeg Kabupaten Tabanan - Anysiah Elly Yulianti; I Wayan Suarta Asmara; I Wayan Sali; I Ketut Aryana (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2019)
Rabies is an acute infectious disease that attacks the central nervous system. This disease is caused by the rabies virus which is transmitted through the bite of rabies transmitting animals such as dogs, cats and apes. This community service aims to improve the understanding of Sekaa Teruna Teruni in the District of Selemadeg Timur, Tabanan Regency, especially in the work area of the Selemadeg Timur Community Health Center II concerning prevention of rabies. The method used was a pre-test and post-test using a questionnaire to determine the level of knowledge of all Sekaa Teruna Teruni about prevention of rabies. The number of targets was 25. There was an increase in the knowledge of the number of inhabitants involved in the prevention of rabies by 31.87%, before presentation/counseling obtained results of 33.36% and after being given presentation/counseling to 65.27%. It is expected that all teruna teruni who have received counseling can provide information to the surrounding community so that they can also know the first prevention and action that can be done when bitten by a rabid suspect dog.Keywords: Sekaa teruna teruni, teens group, knowledge, rabies.